Effect of cognitively engaging physical activity on executive functions in children - Bulten, Rheanna; Bedard, Chloe; Graham, Jeffrey D.; Cairney, John (Frontiers in Psychology, 2022)
Purpose: Physical activity (PA) has been shown to enhance executive functions (EFs) in children, and PA involving a cognitive component may confer additional benefit. The purpose of this study was to investigate whether cognitively engaging physical activity (PA) impacts executive functions (EFs), and whether affect and fitness act as either mediators or moderators of this relationship. Methods: A randomized controlled trial was utilized to assess changes in EFs between a 20-minute Dual Task (intervention condition), a PA Task (control condition), and a Cognitive Task (control condition). Children were scheduled for two visits in the INfant and Child Health (INCH) Lab at the University of Toronto. Physical fitness was assessed using the 20m shuttle run, standing long jump, and grip strength tests. EFs were assessed using the Stroop Task, Trail Making Task, and Forward Working Memory Task. Results: 38 children (Mage=11.95 years, SD=0.49, 61% female) participated. Repeated measures ANOVA showed main interactions between time on inhibition scores (p < .05, p2=.489), and positive affect scores (p < .01, p2=.284). Interaction effects between condition and time were not significant (p = .787, p2=.014, p = .333, p2=.061, p = .799, p2=.013 for inhibition, switching, and passive working memory, respectively). Results showed no significant mediation effect of affect (95% CI = -.5915, 2.147), or moderating effect between fitness and EF changes. Conclusion: Possible explanations for these findings include inadequate cognitive engagement, lack of executive function transfer, and statistical power. Results suggest any of these interventions may be beneficial for improving inhibition and positive affect in children.